Organic-Inorganic Hybrid Planarization and Water Vapor Barrier Coatings on Cellulose Nanofibrils Substrates - Karasu, Feyza; Müller, Luca; Ridaoui, Hassan; Ibn ElHaj, Mohammed; Flodberg, Göran; Aulin, Christian; Axrup, Lars; Leterrier, Yves (Frontiers in Chemistry, 2018)
Cellulose nanofibrils (CNF) can be produced in the form of thin, transparent and flexible films. However, the permeability of such materials to oxygen and water vapor is very sensitive to moisture, which limits their potential for a variety of packaging and encapsulation applications. Diffusion barrier coatings were thus developed to reduce the access of water molecules to enzymatically pre-treated and carboxymethylated CNF substrates. The coatings were based on UV curable organic-inorganic hybrids with epoxy, tetraethylorthosilicate (TEOS) and 3-glycidoxypropyltrimethylenesilane (GPTS) precursors and additional vapor formed SiNx layers. A total of 14 monolayer and multilayer coatings with various thickness and hybrid composition were produced and analyzed. The water vapor transmission rate (WVTR) of the bilayer epoxy/CNF film was two times lower compared to that of uncoated CNF film. This was partly due to the water vapor permeability of the epoxy, a factor of two times lower than CNF. The epoxy coating improved the transparency of CNF, however it did not properly wet to the CNF surfaces and the interfacial adhesion was low. In contrast hybrid epoxy-silica coatings led to high adhesion levels owing to the formation of covalent interactions through condensation reactions with the OH-terminated CNF surface. The barrier and optical performance of hybrid coated CNF substrates was similar to that of CNF coated with pure epoxy. In addition, the hybrid coatings provided an excellent planarization effect, with roughness close to 1 nm, one to two orders of magnitude lower than that of the CNF substrates. The WVTR and oxygen transmission rate values of the hybrid coated CNF laminates were in the range 5–10 g/m2/day (at 38°C and 50% RH) and 3–6 cm3/m2/day/bar (at 23°C and 70% RH), respectively, which matches food and pharmaceutical packaging requirements. The permeability to water vapor of the hybrid coatings was moreover found to decrease with increasing the TEOS/GPTS ratio up to 30 wt% and then increase at higher ratio, and to be much lower for thinner coatings due to further UV-induced silanol condensation and faster evaporation of byproducts. The addition of a single 150 nm thick SiNx layer on the hybrid coated CNF improved its water vapor barrier performance by more than 680 times, with WVTR below the 0.02 g/m2/day detection limit.